Comparison of the Abilities of Different Attenuated Salmonella typhimurium Strains To Elicit Humoral Immune Responses against a Heterologous Antigen - Dunstan, Sarah J. (American Society for Microbiology (ASM), 1998)
We compared the abilities of different Salmonella enterica var. Typhimurium (S. typhimurium) strains harboring mutations in the genes aroA, aroAD, purA, ompR, htrA, and cya crp to present the heterologous antigen, C fragment of tetanus toxin, to the mouse immune system. Plasmid pTETtac4, encoding C fragment, was transferred into the various S. typhimurium mutants, and the levels of antigen expression were found to be equivalent. After primary oral immunization of BALB/c mice, all attenuated strains were capable of penetrating the gut epithelium and colonizing the Peyer’s patches and spleens of mice. Of all strains compared, the ΔpurA mutant colonized and persisted in the Peyer’s patches at the lowest level, whereas the ΔhtrA mutant colonized and persisted in the spleen at the lowest level. The level of specific antibody elicited by the different strains against either S. typhimurium lipopolysaccharide or tetanus toxoid was strain dependent and did not directly correlate to the mutants’ ability to colonize the spleen. The level of immunoglobulin G1 (IgG1) and IgG2a antibody specific for tetanus toxoid was determined in mice immunized with four S. typhimurium mutants. The level of antigen-specific IgG1 and IgG2a was significantly lower in animals immunized with S. typhimurium ΔpurA. Antigen-specific T-cell proliferation assays indicated a degree of variability in the capacity of some strains to elicit T cells to the heterologous antigen. Cytokine profiles (gamma interferon and interleukin-5) revealed that the four S. typhimurium mutants tested induced a Th1-type immune response. Mice were challenged with a lethal dose of tetanus toxin 96 days after oral immunization. With the exception of the S. typhimurium ΔpurA mutant, all strains elicited a protective immune response. These data indicate that the level of total Ig specific for the carried antigen, C fragment, does not correlate with the relative invasiveness of the vector, but it is determined by the carrier mutation and the background of the S. typhimurium strain.